The Improvement of Community Knowledge, Attitudes and Practices After Covid-19 Socialization - Khaerunnisa, Siti; Syafa'ah, Irmi; Wungu, Citrawati Dyah Kencono; Prabowo, Gwenny Ichsan; Handajani, Retno; Safitri, Indri; Notopuro, Harianto; Qurnianingsih, Ema; Lukitasari, Lina; Humairah, Ira; Bakhtiar, Arief; Suwandito, Suwandito; Asih, Susi Wahyuning; Anggraeni, Zuhrotul Eka Yulis; Adi, Ginanjar Sasmito; Nugrahani, Ely Rahmatika; Zulka, Ayesie Natasha; Soetjipto, Soetjipto (Folia Medica Indonesiana, 2021)
This study determined community knowledge, attitudes, and practices after COVID-19 socialization in Rambipuji and Suci Village, Jember District, East Java, Indonesia. This study used the analytic observational design study. As many as 40 people were given socialization about COVID-19 by gathering and online. The questionnaires were completed in two parts included before-socialization and after-socialization. The questionnaire data were analyzed descriptively by calculating frequency, percentage, and inferential statistics by t-test, Spearman correlation, and chi-square test. The data analysis used IBM SPSS version 23 software. The mean and standard deviation of percentage of knowledge pre-test, knowledge post-test, high attitude, moderate attitude, low attitude, very high practice, high practice, sufficient practice, and low practice were 58.33 ± 30.97, 77.70 ± 22.52, 62.5±21.7, 31±22.2, 6.5±17.1, 65±13.8, 32.3±13.8, 1.25±2.4, 1.25±1.8, respectively. Knowledge pre-test and post-test correlated 0.819 (p=0.001) and a t-test with p=0.003. Attitudes and practices correlated with p=0.001. Socialization of COVID-19 was useful to improve the community knowledge, attitudes, and practices in Rambipuji and Suci Village, Jember District, East Java, Indonesia that could prevent the transmission and inhibit the spread of the COVID-19 pandemic in Indonesia. Furthermore, continuous encouragement of COVID-19 socialization in wide areas was recommended.